Surface electromyography control system based on wavelet transform: a review - Mahdavi, Farzaneh Akhavan; Ahmad, Siti Anom (2012)
This paper presents a review of some improvements on Electromyography (EMG) control system with respect to Wavelet analysis. Regarding the vast variety of EMG signal applications such as rehabilitation of people suffering from some mobility limitations, scientists have done much research on EMG control system. Therefore in this area, there are different methods for analyzing EMG signal and the efficiency of EMG recognition systems has been improved. Nevertheless, some of these systems are not consistent with the nature of the EMG signal as a non-stationary signal. Hence, this paper reviews some development of EMG control system concerning Wavelet Transform as a compatible technique with the essence of EMG signal and other methods. Ultimately, the achievement of Wavelet transform is investigated as a powerful tool to analyze EMG signal.